Contribuição ao estudo dos absorvedores dinâmicos de vibrações não-lineares - Borges, Romes Antonio (2008)
In their simplest form, dynamic vibration absorbers (DVAs) are essentially devices of lumped parameters of mass-stiffness-damping that once connected in a given primary structure are capable of absorbing the vibratory energy at the connecting point, providing a reduction of the vibration level. These devices can be used in various configurations and find a number of applications in several areas of engineering. Unfortunately, in the context of nonlinear dynamics, few works had been proposed in the context of the modelling strategies and applications of nonlinear dynamic vibration absorbers (nDVAs). The great advantage of this type of absorber has to do with the suppression bandwidth that is amplified with respect to the one find for the linear absorbers. In the present work, the nonlinear effect is introduced in the stiffness of the system. Then, the interest is devoted to analyzing how this effect can increase the efficiency of this device, for a given interest frequency band. By using the frequency response function of the system, a sensitivity analysis is performed, leading to the most important parameters for design purposes and optimization. Finally, by using genetic algorithms the multi-objective optimization problem is solved, aiming at obtaining a configuration that leads to the largest suppression bandwidth and the maximum vibration reduction, simultaneously. The optimal robust solution is compared with the deterministic one.